Understanding the cost of a new integration of care model for people with severe mental illness served in community mental health clinics - Mangurian, Christina (Psychiatr Serv, 2017)
People with severe mental illness (SMI), such as schizophrenia and bipolar disorder, experience premature mortality, often from cardiovascular disease (CVD). Unfortunately, people with SMI are not screened or treated for CVD risk factors per national guideline recommendations. Access to primary preventive care in community mental health settings has the potential to reduce early mortality rates in people with SMI. The authors review best practices for developing an integration of care model for individuals with SMI by considering economic feasibility and sustainability from the perspective of a community mental health clinic. A process mapping approach was used to gather information on clinic costs (staff roles, responsibilities, time, and salary) in servicing 544 patients at one community mental health clinic. The estimated cost of the model was measurable and modest, with a $74 per-person annual cost, suggesting that this model may be financially feasible.